The Effect of Family Participation in Nutrition Education Intervention on the Nutritional Status of Preschool Age Children - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2019)
To evaluate the effectiveness of family participation in nutrition education intervention on the nutritional status of preschool age children, a 10-week nutrition education program was implemented in 74 children in a public kindergarten. Children were assigned to one of three groups, namely the family participation group (FPG), the education group (EG), and the control group (CG). Interventions included school-based nutrition education, family nutrition education documents and family-child take-home activities and monthly meetings with families in the FPG, school-based nutrition education in the EG, and no intervention in the CG. Anthropometric measurements and a 3-day food record and food group consumption assessment were completed before and after intervention. Intervention led to positive changes in food availability, offering and consumption patterns in FPG and EG, with greater changes in FPG, along with lower obesity prevalence (p < 0.05). Our results show that family participation in a preschool nutrition education program can increase the effectiveness of nutrition education.
Keywords: Nutrition education program; Nutrition; Nutritional status; Family participation; Preschool children; DIET QUALITY; FOOD; CHILDHOOD; KNOWLEDGE; EXPOSURE; PROGRAM; FRUIT; IDENTIFICATION; ASSOCIATIONS; CONSUMPTION